Effect of lifestyle focused text messaging on risk factor modification in patients with diabetes and coronary heart disease: A sub-analysis of the TEXT ME study. (July 2019) - Haider, R.; Hyun, K.; Cheung, N.W.; Redfern, J.; Thiagalingam, A.; Chow, C.K.
Abstract: Aims: There is potential to provide public health interventions through text messaging for patients with Type 2 diabetes mellitus (T2DM). Our objective was to ascertain if lifestyle focused text messaging addressing cardiovascular risk factors in patients with coronary heart disease (CHD) and T2DM, was more effective than usual care. Methods: This is a secondary analysis of the TEXT ME study, a randomised clinical trial of a 6-month text messaging intervention in patients with coronary heart disease. The measured outcomes include cholesterol, blood pressure (BP), body mass index (BMI), HbA1c, waist/hip circumference and smoking status. Our objective was to ascertain if lifestyle focused text messaging in patients with T2DM was more effective than usual care, and to determine if the intervention was more effective in patients with T2DM compared to those without. Results: 229 participants in the TEXT ME study had T2DM (32%), 111 participants in the intervention group and 118 in the control group. At 6 months, the mean difference in systolic BP was −7.6 mmHg (95%CI −11.8, −3.37, p = 0.0003) and diastolic BP −3.7 mmHg (95%CI −6.12, −1.24, p = 0.0032). The mean difference in low density lipoprotein in the intervention arm, compared to the control arm, was −0.05 mmol/L (95%CI −0.27, 0.18, p = 0.813), and in triglycerides was −0.29 mmol/L (95%CI −0.59, 0.01, p = 0.035) respectively. The mean difference in BMI was −0.89 kg/m 2 (95%CI −2.74, 0.95, p < 0.0001) in the intervention group, waist circumference −3.98 cm (95%CI −8.57, 0.61, p < 0.0001) and hip circumference −3.26 cm (95%CI −7.67, 1.16, p = 0.0006). Intervention subjects with diabetes were less likely to be smokers at 6 months. The mean difference in HbA1c between the control and intervention group was not significant (p = 0.126). The intervention was as effective in patients with diabetes, compared to those without. Conclusion: Among patients with coronary heart disease with T2DM, lifestyle-focused text messaging resulted in significant risk factor reduction.